Matters of Steel : Illustrating and Assessing the Deterioration of the World War II Merchant Freighter Caribsea - Fox, Kara Davis (East Carolina University, 2015)
The purpose of this thesis is to acquire historical and archaeological datasets for the illustration and interpretation of site formation processes affecting a World War II merchant shipwreck, and to use this data to develop a series of 3D models displaying sequential shipwreck disintegration. This thesis proposes to explore the potential of a) using archival sources (in particular ship builder’s plans) to create the historical ship model and b) using archaeological resources to create an archaeological ship model, in order to visualize individual multi-stage deterioration. Additionally, by integrating structural deterioration assessments, as well as adding inferred environmental variables (including physical, biological, and chemical processes) into site formation models, resource managers and maritime archaeologists may forecast future site transformations. The interdisciplinary research will include historical and geo-spatially accurate data, combined with the understanding of cultural and environmental processes. It is hoped that an integrated explanatory model designed to visualize cumulative site formation data will contribute towards management actions regarding long-term stewardship of shipwrecks of this type.
Keywords: Archaeology; World history; Merchant marine; Site formation; Virtual archaeology; Archaeological surveying--North Carolina--Lookout, Cape; Archaeology--Methodology; Underwater archaeology--Computer simulation; Underwater archaeology--North Carolina--Lookout, Cape; Shipwrecks--North Carolina--Lookout, Cape; Caribsea (Merchant freighter)